2015
DOI: 10.3923/rjes.2015.355.363
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional Liver and other High Metabolic Organs in Asymptomatic Petroleum Depot Workers in Calabar South-South, Nigeria

Abstract: The health concerns for petroleum workers warranted this study in asymptomatic exposed (n=64) and control (n=64) ) in the exposed group was higher (p<0.05) than that in the control group (11.59±2.10 and 7.53±1.71 μmol LG 1 ) by 97.50 and 134.40%, respectively whereas the computed TB:CB ratio (1.30±1.62) was lower (p<0.05) than that in the control group (1.54±2.33) by 15.58%. Aside the AST:ALT ratio (1.39±1.26) that was lower (p<0.05) than that in the control (2.22±1.84) by 37.39%, the other observations in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Their results showed a significant increase in liver function indices including ALT, AST, ALP, and gamma-glutamyl transpeptidase (GGT) in petroleum depot workers compared to their controls. [15] In a simillar study Wang and coworker reported that male mice which were exposed to various concentration of four different doses of VOCs mixture for consecutively 10 days at 2 h/day decreased significantly erythrocyte count (RBC), platelet (PLT) in peripheral blood in mice. While AST, ALT, and ALP increased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed a significant increase in liver function indices including ALT, AST, ALP, and gamma-glutamyl transpeptidase (GGT) in petroleum depot workers compared to their controls. [15] In a simillar study Wang and coworker reported that male mice which were exposed to various concentration of four different doses of VOCs mixture for consecutively 10 days at 2 h/day decreased significantly erythrocyte count (RBC), platelet (PLT) in peripheral blood in mice. While AST, ALT, and ALP increased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it is well-documented that exposure to vinyl chloride, a historic occupational VOC, was associated with steatohepatitis in rubber plant workers, with some workers exhibiting hemangiosarcoma, a rare form of cancer affecting liver sinusoidal cells (Cave, et al, 2010;Fedeli et al, 2019). Other studies focusing on petroleum and auto-industry workers demonstrated that workers who were occupationally exposed to VOCs such as gasoline and other aromatic hydrocarbons, had higher mean levels of liver test results (ALT, AST and ALP) as well as total and conjugated bilirubin, when compared to non-worker controls (Asefaw et al, 2020;Egbuonu and Nkwazema, 2015;Mohammadi et al, 2010). Similar associations have also been observed in non-occupational exposure settings.…”
Section: Discussionmentioning
confidence: 99%